Phytolits, Starch grains and Andean Crops : The input of the diversity from America to Archaeobotanical research - Musaubach, María Gabriela (2021)
This paper presents preliminary results of the archaeobotanical study of South-Central Andes Culinary Heritage Digital Database. We review Andean crops collection sample and reference collection of starch grains and phytoliths making procedures. Besides, both collections include processed products from these crops (for example, flour, roasted seeds, and mote), which were found and collected from fairs and markets. Finally, samples obtained during our ethnoarchaeological and ethnobotanical fieldwork are incorporated. The collection sample includes, plants in natural or dry state, as well as those already transformed throughout culinary processing. Phytoliths and starch grains are a useful tool to identified which crops were part of ancient food. They are analyzed and described with description and identification protocols used in our archaeobotanical research. Usually, Andean crops are defined as traditional crops, growing on the Andes, with a diverse taxonomy, having in common characteristics such as drought, frost and salinity-resistant. Some of them, such as corn, potatoes, quinoa, beans, among others are produced and consumed by families from the central and south central sector of the Quebrada de Humahuaca (Argentina) at small-scale agriculture. Andean taxa with food uses, its culinary processing knowledge and practices, food serving and consumption are retrieved and systematized in a digital database. These reference materials are relevant for archaeobotanical studies. They also contribute to community bio cultural heritage recovery. Their description and registration allows us not only to catalog them in the JUA Herbarium heritage, but to enhance, visibility, safeguarding and management of South-Central Andes Culinary Heritage.